Employee Turn Over Intention: The Roles of Supervisor Leadership Style, Perceived Supervisor Support and Motivation - lieli suharti; candra setiawati (Indonesian Journal Of Business And Economics, 2018)
The supervisor leadership style and the perceived supervisor support toward motivation play an important role in improving employee motivation, the better motivation will also decrease turnover intention. The purpose of this research is to know the influence of supervisor leadership style, the perceived supervisor support toward motivation and its impact on turnover intention. The type this research was a quantitative research. The population of this research was the employees of production division of a Garment company in central Java  as many as 1057 employees. The samples were 197 respondents. The data were collected by distributing questionnaires. The analysis technique used was quantitative descriptive statistics by using multiple regression test and simple regression. The result of the research showed that the supervisor leadership style and the supervisor perception toward motivation had positive effect. Finally, motivation was found  negatively affecting turnover intention.